Double outlet of right ventricle: imaging spectrum on multi-slice computed tomography - Rana, Yashpal R.; Patel, Dinesh L.; Sheth, Megha M.; Jain, Nitisha A.; Patel, Samir G.; Garachh, Milin N. (International Journal of Research in Medical Sciences, 2020)
Background: Multi-slice computed tomography (MSCT) is the main stay of pre-operative assessment of many complex congenital heart diseases (CHD) in current clinical practice, one of them is double outlet of right ventricle (DORV). DORV is one of the conotruncal anomalies that encompasses a wide spectrum of anatomic malformations in which both the aorta and pulmonary arterial trunk arise entirely or predominantly from the morphologically right ventricle (RV). Purpose of this article is to understand spectrum of DORV and associated types of ventricular septal defect (VSD) on MSCT imaging with special emphasis of usefulness of 3-D volume rendered (VR) images in pre surgical evaluation. Methods: A total of 500 paediatric patients (<18 years old), who had undergone MSCT were studied during the period 2014 to 2019 at the tertiary cardiac care centre. Results: 500 patients having primary/suspicious diagnosis of DORV on echocardiography during the said period were enrolled in the study. All the patients who underwent MSCT scan, were studied in detail for: DORV spectrum, associated types of VSD and its relationship to the semilunar valves. Out of 500 total subjects, subaortic VSD was the most common type of VSD observed (53%), followed by subpulmonic VSD (22%), non-committed VSD (18%) and doubly committed VSD (7%). Associations of pulmonary stenosis, subaortic stenosis and aortic co-arctation with various types of VSDs were addressed. Associated other anomalies were also analysed. Conclusions: Advances in MSCT technology has revolutionized pre-surgical diagnosis, management approach and post-operative follow-up of DORV patients. Excellent image qualities along with 3D volume rendered images help surgeon understand complex morphology of DORV variants and associated types of VSD. Significant reduction in intra and post-operative mortality in DORV patients in current era is result of MSCT technology.